Letter: paradoxical skin eruptions during anti‐TNF‐α treatment of Crohn's disease. Issue 10 (23rd April 2019) - Murphy, Bryan; O'Kane, Donal; McCourt, Collette
Abstract : Linked Content This article is linked to Shivaji et al paper. To view this article, visithttps://doi.org/10.1111/apt.15097 .